PENGARUH MODAL SENDIRI DAN MODAL PINJAMAN TERHADAP SISA HASIL USAHA DENGAN TOTAL ASET SEBAGAI VARIABEL MODERASI (Studi Empiris Pada KSP Kopdit Ikamala Larantuka) - Riska Afrilia, Maria; Mitan, Wilhelmina; Yuneti, Katharina (Jurnal Projemen UNIPA, 2025)
This research investigated and elucidated the effects of equity capital and loan capital on net surplus, with total assets as a moderating variable at Ikamala Larantuka Credit Union. The study utilized an associative quantitative methodology and analyzed the financial statements of Ikamala Larantuka Credit Union as its population. The sampling technique implemented was purposive sampling, with primary data serving as the source for the research. Data collection methods comprised documentation and a literature review. The analysis was conducted using Moderated Regression Analysis (MRA) through the SPSS application. The findings revealed that equity capital negatively impacted net surplus, while loan capital did not exhibit any significant effect on net surplus. Furthermore, total assets moderated (enhanced) the effect of equity capital on net surplus and simultaneously moderated (diminished) the effect of loan capital on net surplus.